Korelacje pomiędzy prawem ochrony konsumentów i polityką konkurencji Unii Europejskiej - Onufer, Aneta (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
This article addresses the question of the relationship between consumer protection law and the EU competition policy. The assessment of this relationship shows that competition and consumer policy are interdependent and their ultimate goal is a consumer and economic welfare. The competition law can be treated as the cornerstone of consumer law. Effective competition policy is crucial for delivering maximum benefits for consumers and widening consumer choice. On the other hand, there is a noticeable infl uence of consumer protection laws on fair trade and well functioning marketplace. The possible interactions between consumer and competition policy are described in the article. Most of them are positive, however, in some situations we can observe a clash of interests of the two disciplines. This also indicates the need for integrated approach to competition and consumer interventions
Keywords: ochrona konsumenta; polityka konkurencji; Unia Europejska